The dialectic of memory and habit: The situation in the 21st century architecture - Rappaport, Alexander (project baikal, 2022)
The author’s two articles are united by the theme of the fate of modern architecture in the context of social changes. The first one analyses the dynamics of history, the change in the rhythm of interpretation of its course, and the mal-synchronization of changes in the world and people. The pace of renewal is organically connected with the pace of habituation. Accordingly, the arguments for or against the preservation or change can also radically change. The de-synchronization of historical changes is a problem which can be solved by architecture and urban planning.
Keywords: architecture; human; pace of renewal and habituation; rhythm of changing; values; pluralization of life; architecture as a source of new unity